Draft Annual Plan 1982-83 Introduction and G. N. Statements Vol. 1 - Government of Tripura (Government of Tripura, 1981)
The Draft Annual Plan for Tripura (1982-83) provides a strategic framework to address the state’s socio-economic challenges, focusing on poverty alleviation, employment generation, agricultural development, and infrastructure enhancement. With a population density of 149 persons per square kilometer and a predominantly rural populace (89%), the plan emphasizes the need for targeted interventions for Scheduled Tribes and Scheduled Castes, who comprise 41% of the population. The proposed outlay of Rs. 7,372.08 lakhs allocates resources across key sectors, including agriculture and allied services (28.7%), water and power development (21%), social and community services (30.9%), industry and minerals (5.6%), and transport and communication (10.5%). Investments in the Minimum Needs Programme (MNP) aim to expand rural electrification, healthcare, education, water supply, and nutrition, with specific targets such as electrifying 1,443 villages, improving road connectivity, and establishing 1,050 adult education centres. Healthcare infrastructure includes rural hospitals, primary health centres, and sub-centres, while nutrition programmes target 70,000 beneficiaries, especially women and children. Rural housing initiatives and environmental improvement schemes are also prioritized to enhance living standards. Cooperative societies, including LAMPS, are strengthened to improve credit access and distribution of essential commodities. The plan underscores a comprehensive and inclusive approach to development, combining infrastructure development, social welfare, and economic participation to promote sustainable growth and improved quality of life for Tripura’s population.
Government of Tripura
Government of Tripura
Keywords: Tripura; State Annual Plan; Agriculture; Rural Development; Minimum Needs Programme; Scheduled Tribes; Scheduled Castes; Infrastructure; Education; Healthcare; Rural Electrification; Poverty Alleviation